A Meta-Analysis of the Effects of Foam Rolling on Performance and Recovery - Wiewelhove, Thimo; Döweling, Alexander; Schneider, Christoph; Hottenrott, Laura; Meyer, Tim; Kellmann, Michael; Pfeiffer, Mark; Ferrauti, Alexander (Frontiers in Physiology, 2019)
Foam rolling is thought to improve muscular performance and flexibility as well as to alleviate muscle fatigue and soreness. For this reason, foam rolling has become a popular intervention in all kinds of sport settings used to increase the efficiency of training or competition preparation as well as to speed post-exercise recovery. The objective of this meta-analysis was to compare the effects of foam rolling applied before (pre-rolling as a warm-up activity) and after (post-rolling as a recovery strategy) exercise on sprint, jump, and strength performance as well as on flexibility and muscle pain outcomes and to identify whether self-massage with a foam roller or a roller massager is more effective. A comprehensive and structured literature search was per-formed using the PubMed, Google Scholar, PEDro, and Cochrane Library search engines. Twenty-one studies were located that met the inclusion criteria. Fourteen studies used pre-rolling, while seven studies used post-rolling. Pre-rolling resulted in a small improvement in sprint performance (+0.7%, g=0.28) and flexibility (+4.0%, g=0.34), whereas the effect on jump (-1.9%, g=0.09) and strength performance (+1.8%, g=0.12) was negligible. Post-rolling slightly attenuated exercise-induced decreases in sprint (+3.1%, g=0.34) and strength perfor-mance (+3.9 %, g=0.21). It also reduced muscle pain perception (+6.0%, g=0.47), whereas its effect on jump performance (-0.2%, g=0.06) was trivial. Of the twenty-one studies, fourteen used foam rollers, while the other seven used roller massage bars/sticks. A tendency was found for foam rollers to offer larger effects on the recovery of strength performance (+5.6%, g=0.27 vs. -0.1%, g=-0.01) than roller massagers. The differences in the effects between foam rolling devices in terms of pre-rolling did not seem to be of practical relevance (overall performance: +2.7 %, g=0.11 vs. +0.4%, g=0.21; flexibility: +5.0%, g=0.32 vs. +1.6%, g=0.39). Overall, it was determined that the effects of foam rolling on performance and recovery are rather minor and partly negligible, but can be relevant in some cases (e.g., to increase sprint performance and flexibility or to reduce muscle pain sensation). Evidence seems to justify the widespread use of foam rolling as a warm-up activity rather than a recovery tool.